Efficacy and safety of percutaneous left atrial appendage closure in chronic kidney disease patients with atrial fibrillation : results of a 7-year registry - Vieira, Miguel Bigotte (2019)
© The Author 2017. Published by Oxford University Press on behalf of ERA-EDTA. All rights reserved.